Development of Village Profile to Optimize Local Potential and Improve Community Welfare in Pait Village, Kasembon District, Malang Regency - M. Aris Ichwanto; Joko Samodra; Heru Wahyu Herwanto; Amir Rofiudin; Ary Agung Wibowo; Luhur Adi Prasetya; Salsabila Thifal Nabil Haq; Rian Syahmulloh Hendranawan; Irva Widiyawati; Khusnul Muttaqiyah; Denny Martin; Suhendri Suhendri (Universitas Negeri Malang, 2025)
This community service aims to develop a comprehensive profile of Pait Village, Kasembon District, Malang Regency, to support the management of local potential and improve community welfare. The Participatory Rural Appraisal (PRA) method was used with a participatory approach involving residents in data collection through observations, interviews, focus group discussions (FGDs), and questionnaires. The results show that the infrastructure of Pait Village is generally good, but road lighting needs to be improved for safety. The village's main economic potential lies in the plantation sector (durian, coffee and dairy) and BUMDes businesses such as batik, which require wider marketing support. In addition, Pait Village's natural tourism potential is promising but requires a better management strategy. Local wisdom such as the tradition of gotong royong and traditional rituals form the basis of the village's sustainable development. Residents show high interest in modern agriculture and entrepreneurship training to improve skills and income. The village profile video produced from this activity serves as a promotional medium to attract investors and tourists. Recommendations include improving street lighting, developing BUMDes businesses and community-based tourism, as well as ongoing training in agriculture and entrepreneurship. The results of this service are expected to help Pait Village become an independent and competitive village that still maintains local wisdom.